Study of Dipolar Direct Current Excitation Driven-Collision Induced Dissociation Processes in Digital Ion Traps - ZHOU Wen-xing1,2;HUANG Gang2;CAI Hong-hua2;LIU Jun-jie2;DENG Yi-bing3;YANG Qing-yu1;WANG Wei-min4;XU Fu-xing4;DING Chuan-fan4 (Zhipu Xuebao, 2023)
The development of fragment ion detection is significant for improving the analysis capacity of mass spectrometry. Fragmentation technique has been widely used in the identification of peptides and top-down/bottom-up proteomics analysis. To date, collision-induced dissociation (CID) remains the most commonly used ion activation method in MS/MS experiments, but the effectiveness of CID in ion trap mass spectrometer is limited by low mass truncation and weak fragmentation yield. Recently, technological advances have made the CID process in the ITMS more flexible. The CID process in an ion trap mass spectrometry (ITMS) is usually achieved by superimposing a small auxiliary alternating current (AC) voltage on the main radio frequency (RF) voltage. When the frequency of AC is close to or equal to the lifetime frequency of the isolated ions, the ions are resonantly excited, resulting in a dramatic increase in the kinetic energy of the ions. The high kinetic energy ions will then collide with the background gas, converting the kinetic energy into the internal energy of the ions. Eventually, when the internal energy of the ion is greater than the potential barrier of a bond breaking, a series of fragmentation ions will be formed. In theory, controlling the qvalue is essential to maintain the fragmentation efficiency and trapping efficiency of tandem MS/MS, thus improving the detection of fragmentation ions, while currently reported techniques typically require complex circuitry and often yield different CID modes. In this paper, the effective improvement of fragment ion detection by developing the dipole direct current excitation-collision induced dissociation (DDC-CID) technique was demonstrated, which was implemented on a digital ion trap mass spectrometer by adjusting the duty cycle during CID, or specifically, by increasing the dipole direct current (DC) voltage during CID. The use of pulsed switches and square wave voltages in the digital ion trap technique was a good solution to the problem of circuit design for frequency scanning ion traps. With the DDC-CID technique, the fragmentation efficiency of precursor ions could be improved marginally, with at least 3-fold increase in capture efficiency for low mass fragmentation ions and 1.2-fold increase in fragmentation efficiency for reserpine molecules. These experimental results could also be verified by simulations, where plots of ion trap stability changes indicated changes in ion q-values. In any case, DDC-CID provides an idea and a solution for the low efficiency of fragment ion detection during tandem MS/MS analysis, which will certainly be useful in the future.